2022
DOI: 10.3390/life12091454
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Nitric Oxide and Silicon Applications Alleviate Water Stress in Apricots

Abstract: Many plants confront several environmental stresses including heat, water stress, drought, salinity and high-metal concentrations that are crucial in defining plant productivity at different stages of their life cycle. Nitric oxide (NO) and Silicon (Si) are very effective molecules related in most of them and in varied biochemical events that have proven to be protective during cellular injury caused by some stress conditions like water stress. In the current work, we studied the effect of Si and NO alone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Therefore, humic acid could mitigate the negative effects of Cd stress on morphological, physiological and biochemical parameters in wheat plants [62]. The effects of HA, Si and NO treatments were also detected by some authors [34,63,64], who stated that their treatment promoted plant development and oxidative stress tolerance in plum, apricot and strawberry.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, humic acid could mitigate the negative effects of Cd stress on morphological, physiological and biochemical parameters in wheat plants [62]. The effects of HA, Si and NO treatments were also detected by some authors [34,63,64], who stated that their treatment promoted plant development and oxidative stress tolerance in plum, apricot and strawberry.…”
Section: Discussionmentioning
confidence: 84%
“…The determination of relative water content (RWC) in G. uralensis seedlings leaves followed the protocol outlined by Bakır et al RWC false( % false) = 100 % × false( W f W d false) / false( W t W d false) where W f represents the fresh weight, W t represents the saturated fresh weight, and W d represents the dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters examined here were found to be consistent with the literature. In previous studies examining garlic and onion (Shalaby and El-Ramady, 2014;Sitaula et al, 2020;Kibar, 2022), potato (Röder et al, 2018), apricot (Bakır et al, 2022), and vegetable, the leaves of which are consumed such as mellow, lettuce, and spinach (Chen et al, 2016;Greenwell and Ruter, 2018) Table 5. Effects of L-GLU treatments on bulb yield and ash (%) contents of garlic samples (100 GLU: 100 mg L -1 L-Glutamic acid, 200 GLU: 200 mg L -1 L-Glutamic acid; 400 GLU: 400 mg L -1 L-Glutamic acid; 800 GLU: 800 mg L -1 L-Glutamic acid; 1000 GLU: 1000 mg L -1 L-Glutamic acid; ± Standard errors of three repeat experiments) Effects of L-GLU treatments on total soluble amino acid, total nitrate, total polyphenol, and ascorbic acid contents of garlic…”
Section: Effects Of L-glu Treatments On Bulb Yield In Garlicmentioning
confidence: 99%
“…Researchers reported that, in comparison to NH 4 + , three times more energy is consumed during the assimilation of NO 3 (Cheng et al, 2016;Zhang et al, 2019). Hence, exogenous amino acid treatments might offer advantages in increasing the plant yield and stimulating the resistance to stress (Hildebrandt, 2018;Haghighia et al, 2020;Bakır et al, 2022). Since glutamic acid is an important ammonium recipient, it transforms into other amino acids such as proline, glycine, and arginine, as well as playing important roles in chlorophyll synthesis, activation of vegetal hormones, cell division, and phytochelatin activities (Sun et al, 2019;Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation